Atividades físicas de lazer por universitários: inquéritos repetidos nos anos de 2010, 2012 e 2014 - Sousa, Thiago Ferreira de (2020)
The aim of this study was to compare the proportions of practices of different types of leisure-time physical activities by college students in 2010, 2012 and 2014. Three repeated surveys conducted with college from a higher education institution from state Bahia, Brazil. The modalities were measured through a questionnaire validated for application in college, having been the following types: cycling, volleyball, swimming, treadmill walking, water aerobics, surfing, walking in local places, soccer, basketball, handball, outdoor running, aerobics gymnastics, fights or martial arts, tennis, weight training, treadmill running and general gymnastics using weights and trampolines. As comparisons performed via chi-square test for linear trend. The level of significance was 5%. Participated 1,084, 1,085 and 1,041 college students in 2010, 2012 and 2014, respectively. The most practiced modality in the three surveys was about weight training, followed by soccer. The practice of outdoor running (2010 = 6.9%; 2012 = 8.8%; 2014 = 11.0%) and martial arts (2010 = 4.2%; 2012 = 4.5%; 2014 = 7.6%) increased throughout the investigations. There was a decrease in the practice of gymnastics (2010 = 3.7%; 2012 = 1.9%; 2014 = 1.4%; p = 0.001). It can be concluded that the trend of leisure-time physical activities over time among college students was different according with the type of modalities, with an increase in practitioners of fights or martial arts and running, and decrease in the number of gymnastics practitioners using weights and trampolines.